2012
DOI: 10.1111/j.1742-481x.2012.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of autologous platelet rich fibrin in urethracutaneous fistula repair: preliminary report

Abstract: Urethrocutaneous fistula (UCF) is one of the most common complications occurring after hypospadias repair. Despite the surgical advancement in hypospadias, multiple failed fistula closures are commonly referred to paediatric urologists. Although several techniques have been described to interpose a waterproof layer between urethral and skin closures, occurrence of urethrocutaneous fistula cannot be eliminated completely. In addition to several local tissue grafts, autologous and homologous fibrin sealants are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 13 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…(16) Although one-stage repair is effective in certain cases with proximal hypospadias, (17,18) many surgeons still prefer a staged approach when moderate to severe chordee is present to obtain appropriate straightening and lengthening of the penis at the time of the first-stage surgery. (18)(19)(20)(21) Using a large series of hypospadias patients with marked chordae, we compare the results of a singlestage hypospadias treatment with those of a twostage hypospadias repair. Patients with hypospadias ranging from mild to severe were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Although one-stage repair is effective in certain cases with proximal hypospadias, (17,18) many surgeons still prefer a staged approach when moderate to severe chordee is present to obtain appropriate straightening and lengthening of the penis at the time of the first-stage surgery. (18)(19)(20)(21) Using a large series of hypospadias patients with marked chordae, we compare the results of a singlestage hypospadias treatment with those of a twostage hypospadias repair. Patients with hypospadias ranging from mild to severe were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study by this group demonstrated increased angiogenesis behind these improved outcomes [ 38 ]. Meanwhile, a case report described using platelet-rich fibrin—which generally contains a mix of TGF-B, VEGF, and EGF—placed directly on the urethra of a single pediatric patient who subsequently developed no fistula, an intriguing though far from conclusive report [ 39 ]. Overall, the impact of GFs on urethral healing demonstrates promise for future therapies, but prior to this study there has been no opportunity to compare the impact between GFs.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous platelet concentrate (APC) is a safe product for wound healing, soft tissue reconstruction and bone healing [ 13 , 14 ]. It was first used in hypospadias surgery for the closure of UCF by Soyer et al [ 15 ]. Guinot A et al [ 16 ] was the first to use an autologous platelet-rich fibrin membrane for urethroplasty coverage with encouraging results.…”
Section: Introductionmentioning
confidence: 99%